ASTM designation D2667-95 : Standard test method for biodegradability of alkylbenzene sulfonates. (West Conshohocken (Pa.) : ASTM International)
1.1 This test method covers the determination of the degree of biodegradability of alkylbenzene sulfonates. It serves as an index of the suitability of the sulfonate for general use as a surfactant. 1.2 In general, this test method distinguishes between sulfonates in which the alkyl side chains are linear and those in which they are branched, since the former are more readily biodegradable. If the alkylbenzene sulfonate in fully formulated products is to be examined, it must be extracted using the method noted in Annex A1. (See Appendix X1 for data.)
Keywords: Normen